2021
DOI: 10.3390/curroncol28050357
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of First-Line Pembrolizumab in Older Adults with PD-L1 Positive Non-Small Cell Lung Cancer: A Retrospective Cohort Study of the Alberta Immunotherapy Database

Abstract: The emergence of immunotherapy revolutionized the treatment of non-small-cell-lung cancer (NSCLC), with multiple landmark clinical trials establishing the efficacy of these agents. However, many patients who receive immunotherapy in clinical practice would be considered clinical trial ineligible. One such population that is often under-represented in clinical trials is older adults. In the current study, we evaluated clinical and safety outcomes in this population. Overall, older adults (>70 years of age) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
3
11
1
Order By: Relevance
“… 16 Some studies have suggested that irAEs occur with no significantly different incidence between older and younger adults. 32 , 33 , 34 Older NSCLC patients in our study, however, were observed to have a higher incidence of pneumonitis, hypothyroidism, AKI, and arrhythmia compared with the study evaluating younger patients. 16 This suggests unique characteristics of the incidence irAEs among older patients that may be attributed to the impairment of their immune systems or dysfunction in particular organs.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“… 16 Some studies have suggested that irAEs occur with no significantly different incidence between older and younger adults. 32 , 33 , 34 Older NSCLC patients in our study, however, were observed to have a higher incidence of pneumonitis, hypothyroidism, AKI, and arrhythmia compared with the study evaluating younger patients. 16 This suggests unique characteristics of the incidence irAEs among older patients that may be attributed to the impairment of their immune systems or dysfunction in particular organs.…”
Section: Discussioncontrasting
confidence: 81%
“…Although the limitations of the database used for the current study prevent robust direct comparisons between older and younger adults, it is worth noting that the incidence of any irAEs in our study was similar to that reported in a large retrospective study of younger NSCLC patients 16 . Some studies have suggested that irAEs occur with no significantly different incidence between older and younger adults 32–34 . Older NSCLC patients in our study, however, were observed to have a higher incidence of pneumonitis, hypothyroidism, AKI, and arrhythmia compared with the study evaluating younger patients 16 .…”
Section: Discussionsupporting
confidence: 76%
“…46 Specifically, the association of BMI with clinical outcomes in immunotherapy has been studied previously, and results have shown that patients with higher BMI (ranging from $22 to 25 kg/m 2 ) and obesity have been associated with improved clinical outcomes of significantly higher OS, PFS, and TTD compared with patients who are not overweight. [34][35][36][37][38][39][40][41] Similarly, in this study, patients who had a higher BMI of $25 kg/m 2 were also found to have a significantly improved PFS (P5.01) and TTD (P5.02) but not OS compared with those who had a BMI of ,25 kg/m 2 . In preclinical studies, obesity was associated with a proinflammatory status and upregulation of PD-1 and PD-L1 expression 47 and was clinically shown to increase the risk of immune-related adverse events.…”
Section: Discussionsupporting
confidence: 70%
“…Clinical factors such as weight changes, BMI, and the presence of cachexia have been shown in the past to be associated with outcomes in patients with NSCLC who are treated with immunotherapy. [34][35][36][37][38][39][40][41][42][43][44][45] With the production of inflammatory cytokines by the immune system resulting in the multifactorial syndrome of anorexia, weight and muscle loss, and functional impairment, those with cachexia experience worse survival. [42][43][44][45] This is a key understudied and poorly understood factor that is faced clinically in the real-world setting for patients with advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, age is quite associated with immunotherapy response ( 49 ) because the elderly patients will always be coupled with poor function of T cells and aggressive T cell exhaustion. In addition, we performed an analysis to determine whether age is a prognostic factor in patients with NSCLC receiving ICI.…”
Section: Resultsmentioning
confidence: 99%